2015
DOI: 10.1111/aos.12801
|View full text |Cite
|
Sign up to set email alerts
|

Improving the anti‐inflammatory effect of serum eye drops using allogeneic serum permissive for regulatory T cell induction

Abstract: ABSTRACT.Purpose: To investigate the cytokine composition and anti-inflammatory effects of allogeneic serum preparations for improved use as serum eye drops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 30 publications
1
27
0
3
Order By: Relevance
“…PA by design produces PLTs with minimal WBC content, which may explain why higher IFN‐γ levels have been reported in preparations such as two‐step centrifugation PLT‐rich plasma samples . One substantial outlier was, however, observed in this study, which is well in line with previous observations from healthy blood donors …”
Section: Discussionsupporting
confidence: 91%
“…PA by design produces PLTs with minimal WBC content, which may explain why higher IFN‐γ levels have been reported in preparations such as two‐step centrifugation PLT‐rich plasma samples . One substantial outlier was, however, observed in this study, which is well in line with previous observations from healthy blood donors …”
Section: Discussionsupporting
confidence: 91%
“…Autologous serum eyedrops are recommended for severe dry eyes, as they contain many nutrients and proteins which can improve the extracellular matrix of the ocular surface epithelial cells by facilitating ocular surface maintenance and healing (International Dry Eye WorkShop 2007b). One study found that the anti-inflammatory cytokines were higher in serum from non-dry eye people compared to dry eye patients (Stenwall et al 2015). However, a case-control study reported that there were no significant differences in total antioxidant potential and concentration of ROS in controls and patients with dry eyes (Gus et al 2016).…”
Section: Clinical Relevancementioning
confidence: 99%
“…One study found that the anti‐inflammatory cytokines were higher in serum from non‐dry eye people compared to dry eye patients (Stenwall et al. ). However, a case–control study reported that there were no significant differences in total antioxidant potential and concentration of ROS in controls and patients with dry eyes (Gus et al.…”
Section: Clinical Relevancementioning
confidence: 99%
“…It is accompanied by ocular symptoms in which unstable tear lm, hyperosmolarity, ocular surface in ammation and damage, and neurosensory abnormalities play pathologic roles [5]. Its etiologies include causes secondary to systemic autoimmune disorders such as Sjogren's syndrome, rheumatoid arthritis, systemic lupus erythematous, and so on that are bothersome to doctors and patients [6][7][8][9][10]. In conventional treatment, arti cial tear eye drops are mainly used to moisturize the ocular surface and offer additional lubrication [11].…”
Section: Introductionmentioning
confidence: 99%